2007
DOI: 10.1002/ardp.200700007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Isomerization, and Antimicrobial Evaluation of Some Pyrazolopyranotriazolopyrimidine Derivatives

Abstract: 6-Amino-5-imino-pyrazolo[4',3':5,6]pyrano[2,3-d]pyrimidine derivative 4 and pyrazolo-[4',3':5,6]pyrano[2,3-d]pyrimidin-5-ylhydrazine derivative 5 were prepared starting from 6-amino-3-methyl-4-(p-nitrophenyl)-2,4-dihydropyrano[2,3-c]pyrazole-5-carbonitrile 1. The synthesis and structure characterization of 9,11-dihydropyrazolo[4',3':5,6]pyrano[3,2-e][1,2,4]triazolo[4,3-c]pyrimidine derivatives 7 and 9 and their isomerization to 9,11-dihydropyrazolo[4',3':5,6]pyrano[3,2-e] [1,2,4]triazolo[1,5-c]pyrimidine deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) measurement was determined for compounds with significant growth inhibition zones using twofold serial dilution method. [32] The MIC (µg/mL) and inhibition zone diameters values are presented in Table 1. The results depicted in Table 1 revealed that most of tested compounds displayed variable inhibitory effects on the growth of the tested Gram-positive and Gram-negative bacterial strains and also against antifungal strains.…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) measurement was determined for compounds with significant growth inhibition zones using twofold serial dilution method. [32] The MIC (µg/mL) and inhibition zone diameters values are presented in Table 1. The results depicted in Table 1 revealed that most of tested compounds displayed variable inhibitory effects on the growth of the tested Gram-positive and Gram-negative bacterial strains and also against antifungal strains.…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%
“…Minimum inhibitory concentration (MIC) of the most active synthesized compounds 3a, 5a and 5c was evaluated in vitro using the related reference [21]. The results of minimum inhibitory concentration were depicted in Table 2.…”
Section: Mic Of the Most Active Compoundsmentioning
confidence: 99%
“…The plates were incubated at 24 h at 37 ºC for bacteria and 48 h at 37 ºC for fungi. Compounds that showed signicant growth inhibition zones (>14 mm) using the twofold serial dilution technique, 31 were further evaluated for their minimal inhibitory concentrations (MICs).…”
Section: In Vitro Antimicrobial Activity Antimicrobial Evaluationmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) measurement was determined for compounds showed significant growth inhibition zones (>14 mm) using twofold serial dilution method. 31 The MIC (mg/ml) and inhibition zone diameters values are recorded in Table 4.…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%